2021
DOI: 10.3390/ijms22126417
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of the Evolution of Extracellular Vesicles’ Knowledge: From 1946 to Today

Abstract: Extracellular vesicles (EVs) are a family of particles/vesicles present in blood and body fluids, composed of phospholipid bilayers that carry a variety of molecules that can mediate cell communication, modulating crucial cell processes such as homeostasis, induction/dampening of inflammation, and promotion of repair. Their existence, initially suspected in 1946 and confirmed in 1967, spurred a sharp increase in the number of scientific publications. Paradoxically, the increasing interest for EV content and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 70 publications
0
72
0
3
Order By: Relevance
“…Exosomes derived from the same parent cell would be expected to contain an analogous protein, nucleic acid, and lipid composition, though it has recently been shown that the molecular composition of exosomes can differ even when the exosomes derive from the same primary cell [ 1 ]. These microvesicles contain different biomarkers, proteins, and lipids such as sphingomyelin, cholesterol, phosphatidylserine, and ceramide [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Exosomal Cargomentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes derived from the same parent cell would be expected to contain an analogous protein, nucleic acid, and lipid composition, though it has recently been shown that the molecular composition of exosomes can differ even when the exosomes derive from the same primary cell [ 1 ]. These microvesicles contain different biomarkers, proteins, and lipids such as sphingomyelin, cholesterol, phosphatidylserine, and ceramide [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Exosomal Cargomentioning
confidence: 99%
“…The biogenesis of exosomes begins with endocytosis to form early endosomes by inward budding, then form late endosomes, and ultimately produce multivesicular bodies (MVBs). MVBs merge with the cell membrane and, by exocytosis, release exosomes into the extracellular environment [ 1 ]. Exosomes modulate the recipient cell’s gene expression by initiating cell signaling as well as intercellular transfer of the protein, lipid, and RNA cargo, not only in a functional setting (blue exosomes in the picture) but also in cancer (gray exosomes), infectious (red exosomes), and parasitic (yellow exosomes) diseases, gaining clinical significance because of their potential use as biomarkers or next-generation therapeutics [ 11 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we clarified the molecular basis of GABA-induced gut–brain interactions and reported that exosomes derived from GABA-treated intestinal cells serve as signal transducers that mediate brain–gut interactions [ 24 ]. Exosomes are a family of particles released from the cell that are delimited by a lipid bilayer, and attention has recently been focused on the role of exosomes as biomarker candidates for diagnosis, prognosis and even therapeutic tools of various diseases [ 25 ]. In the present study, we clarified that exosomes derived from serum of mice administered GABA as well as from GABA-treated Caco-2 cells activated neuronal cells, and that GABA administration changes the expression of memory-related genes in hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extracellular vesicles (EV) have gained attention in the context of neuroinflammation and mental disorders [ 9 ]. EVs are defined as small lipid bilayer particles that originate from various cell types and carry molecular cargo throughout the circulation to distant cells [ 10 ]. It has been suggested that EVs circulating in bodily fluids may be of use for the diagnosis and treatment of mental disorders [ 11 ], and they may also be linked to the physiological response to mental and social stress.…”
mentioning
confidence: 99%